KOMUNIKASI VERBAL ANAK PESISIR USIA 7-8 TAHUN PADA TRANSAKSI PENJUALAN PRODUK KEBUDAYAAN DENGAN TURIS MANCANEGARA - Rustan, Edhy; Subhan, Subhan (Jurnal Pendidikan Usia Dini, 2018)
This study aims to obtain a description of children’s second language verbal communication skills aged 7-8 years in the activity of buying and selling transactions with foreign tourists. This research was conducted in South Coastal Coast of Central Lombok Regency of West Nusa Tenggara. This research is a qualitative study of case study by Milles and Hubberman model data analysis technique with four stages of interalain analysis (1) data collection, (2) data reduction, (3) data display and (4) drawing conclusion. The results of this study indicate that the verbal communication skills of coastal children are obtained partially covering three linguistic components; vocabulary, shipping and grammatical arrangement. The process of acquiring verbal communication skills is influenced by two factors, namely family pressure and self-exposure of children to the coastal tourism environment that encourages children to sell cultural products to foreign tourists. For these purposes, coastal children use two common patterns of second language verbal communication, ie direct verbal communication patterns (spoken word) and indirect verbal communication patterns (writing word). Keyword: Verbal communication skill, Children aged 7-8 years. Penelitian ini bertujuan untuk memeroleh gambaran kemampuan komunikasi verbal bahasa kedua anak usia 7-8 tahun dalam kegiatan transaksi jual beli dengan turis mancanegara. Penelitian ini dilakukan di Pesisir Pantai Selatan Kabupaten Lombok Tengah Nusa Tenggara Barat. Penelitian ini adalah studi kasus dengan teknik analisis data model Milles dan Hubberman dengan empat tahapan analisis yang meliputi (1) pengumpulan data, (2) reduksi data, (3) display data, dan (4) penarikan kesimpulan. Hasil analisis menunjukkan bahwa kemampuan komunikasi verbal anak pesisir pantai cenderung diperoleh secara parsial; mencakup tiga komponen kebahasaan antaralain kosakata, pelafalan dan susunan gramatikal. Adapun proses pemerolehan kemampuan komunikasi verbal tersebut dipengaruhi oleh dua faktor yaitu tekanan keluarga dan ekspos diri anak pada lingkungan pariwisata pantai yang mendorong anak untuk berjualan produk-produk kebudayaan kepada para turis mancanegara. Untuk kepentingan tersebut, anak pesisir pantai menggunakan dua pola umum komunikasi verbal bahasa kedua, yaitu pola komunikasi verbal langsung (spoken word) dan pola komunikasi verbal tidak langsung (writing word). Kata Kunci: kemampuan komunikasi verbal, anak usia 7-8 tahun